2015
DOI: 10.1515/jppr-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Phytophthora infestans (Mont.) de Bary on potato and tomato in Maine, 2006–2010

Abstract: Late blight, caused by Phytophthora infestans (Mont.) de Bary, is a devastating disease which is found worldwide. In Maine, United States (US), we recorded late blight on potato and tomato during the 2006-2009 cropping seasons. From 2006 to 2008, over 90% of the diseased samples were collected in potato fields from northern and central Aroostook County in Northern Maine, US. Then, in 2009, an unprecedented influx of inoculum on infected tomato transplants shipped to retail garden centers throughout the Northea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The climatic data recorded and observed for the 2009 cropping year showed a broader distribution of RH compared to the 2005 to 2008 years, and indicated that climatic variations may occur from year to year. Variations in temperature and relative humidity values and their conduciveness for late blight development have been previously documented (Olanya et al 2015). The numerically lower solar radiation, temperatures, and relative humidity values at the potato canopy at the Presque Isle site compared to published data, suggests that conditions for pathogen survival were more conducive at Presque Isle than that recorded in the published data of Sunseri et al 2002.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The climatic data recorded and observed for the 2009 cropping year showed a broader distribution of RH compared to the 2005 to 2008 years, and indicated that climatic variations may occur from year to year. Variations in temperature and relative humidity values and their conduciveness for late blight development have been previously documented (Olanya et al 2015). The numerically lower solar radiation, temperatures, and relative humidity values at the potato canopy at the Presque Isle site compared to published data, suggests that conditions for pathogen survival were more conducive at Presque Isle than that recorded in the published data of Sunseri et al 2002.…”
Section: Discussionmentioning
confidence: 75%
“…The occurrence of SSP was consistent with favorable conditions for spore survival and implied that late blight outbreaks may be expected under such conditions. Previous research that assessed the incidence of late blight on potato and tomato in Maine (Olanya et al 2015), indicated that the frequencies of late blight outbreaks were substantially greater when temperatures and relative humidity were favorable. This is in agreement with the possibility that sporangia survival potential would be greater during such conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them collar rot or Sclerotium wilt; Sclerotium rolfsii (Mahato et al 2017) [22] , damping off; Fusarium spp., Pythium spp., Rhizoctonia solani, Sclerotium rolfsii (Prasad et al 2017) [33] , early blight; Alternaria solani (Roopa, 2012) [39] , Fusarium wilt; Fusarium oxysporum f.sp. lycopersici (Manikandan and Raguchander, 2014) [23] , late blight (Olanya et al 2015) [30] , Septoria leaf spot (Parker et al 1997 andBlum, 2000) [31,11] , bacterial fruit canker; Clavibacter michiganensis subsp. michiganensis (Ftayeh et al 2010 andSharabani et al 2013) [18,41] , bacterial wilt; Ralstonia solanacearum (Ayana and Fininsa, 2016) [9] , bud blight; Groundnut bud necrosis virus (Manjunatha et al 2010) [24] , leaf curl; Tomato leaf curl virus (Shelat et al 2014 andYadav et al 2014) [42,48] , tomato mosaic; Tomato mosaic virus (Alishiri et al 2013) [4] , tomato spotted wilt; Tomato spotted wilt virus (Sevik and Arli-Sokmen, 2012) [40] and Root knot; Meloidogyne spp (Naz et al 2012) [28] are major diseases of tomato (Mahato et al 2017) [22] .…”
Section: Introductionmentioning
confidence: 99%